Some aspects of estate duty on deceased estates in the Republic of South Africa: with special reference to the problems and effects of double taxation occuring in relation to the German Erbschaftsteuergesetz (Inheritance Tax Act) - Beckmann, Nicolai Friedrich (Department of Commercial Law, 2021)
'In this world nothing can be said to be certain, except death and taxes'. If one agreed with this statement, made by Benjamin Franklin one year prior to his death, one could come to the ultimate conclusion that there has to be a special certainty about capital transfer taxes, estate duties, inheritance taxes or other death duties levied on deceased estates. There seems to be no reason whatsoever to doubt the final truth of the first part of Franklin's statement. But is it also right to assume that there is a certainty about taxes or, what is more, to draw the conclusion that there could be a special certainty about the different types of taxes connected with the death of an individual? On the one hand it seems to be true. There are only a few countries throughout the world levying very limited or no taxes at all, and if one forgets about a few tax havens, like the Caymen Islands for example, one is also inclined to agree with the latter part of Franklin's statement - there seems to be certainty about the levying of taxes. But, on the other hand, is the amount of taxes, especially the amount of capital transfer taxes, estate duties, inheritance taxes or other death duties levied on a persons death, always that certain? The avoidance of double taxation has been an objective of most of the world's nations since the negotiation of the first Income Tax Convention in the middle of the nineteenth century. The development of most of the world's countries into modern industrial nations, with trade links all over the world, gradually demonstrated the problems which can arise if one country levies taxes without considering the levying of an equal or similar tax in another country. Today the negative consequences of double taxation on the movement of goods, services and capital are widely understood by modern states enacting tax systems for their citizens.